Penggunaan Model Problem Based Learning (PBL) Untuk Meningkatkan Hasil Belajar Siswa Kelas V Sekolah Dasar - Julvi, M. Alfida; Mansurdin, Mansurdin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2024)
The low learning outcomes of the students are the impetus behind this study's problem. The purpose of this study is to describe how the Problem Based Learning (PBL) Model improved student learning outcomes in integrated thematic learning. A qualitative and quantitative approach is taken. Classroom action research, also known as CAR, consists of four stages: Implementation, Observation, and Evaluation There were a total of 16 students and teachers who participated in this study. The procedures and outcomes of utilizing the PBL model to implement integrated thematic learning are data sources. Tests and non-tests are the instruments used for data collection. From cycle I to cycle II, the results showed an increase in integrated thematic learning outcomes, including: 1) Evaluation of example plan for cycle I 83.25%, to 94% in cycle II. ( 2) Cycle I assessment of the teacher aspect: 82%; cycle II assessment: 96%. 3) In cycle I, students were evaluated at a rate of 82 percent, while in cycle II, students were evaluated at 96 percent. 4) Learning outcomes were assessed at 76.5 percent in cycle I and 85 percent in cycle II. It may indicate that the PBL model can enhance student learning outcomes.